The influence of gender and marital duration on the perception of martial problems professionals in Sabah - Lee Chee Keong (2004)
The aim of this study was to investigate the influence of gender and marital duration on the perception of marital problems of professionals; and to provide local data for the planning of premarital and marital continuing programs. Employing a convenient sample of 359 married working professionals (279 males and 80 females) in Sabah and through a postal suNey; the participants were asked to indicate using a 7-point Likert scale, how likely they will meet 37 issues at the current stage of their marriage as marital problems. The mean score of these 37 issues was used as the index of perception of marital problems. Using multiple regression analysis, with number of children, highest educational achievement and employment status as control variables; no gender difference was found in the perception of marital problems (t= 1. 7 46, p=. 082). Marital duration was negatively correlated to the index of perception, F(S,331)=2.446, p=-.034, R square=-.036, Standardized Beta=-.198, t=-3.018, p=.003. The interacting factor of gender and marital duration had no statistical significant correlation with the outcome variable, F(4,332)=.981, p=.480. The participants were a/so asked to indicate five most damaging issues to marriage. Four of the five most damaging issues perceived by both male and female participants were the same, namely Infidelity, Problematic behavior, Physical violence, and Budget/ Finances. The fifth issue mentioned by male participants was Incest, and by female participants was Communication. Limitations of this study such as sampling method, low response rate (28%) and the crudeness of the measuring instrument have reduced the usefulness of the data. To improve the explanatory power of the regression models, further investigations need to include measures of gender attitude and marital quality as predictors to better explain the variance in the perception of marital problems. Better sampling method, larger samples and more heterogeneous subjects in future investigations should help to verify or refute the findings of this study.